Answer equals 1
Step-by-step explanation:
It's not a hard question
Answer:
f (x) = -2 (x + 6)^2 + 2
Step-by-step explanation:
f (x) = -2x^2 - 24x - 70 <--- divide out -2 out of the first two terms...
f (x) = -2 (x^2 + 12x) - 70 <-- divide the x coefficient by 2 and then square it, then add AND subtract it)
f (x) = -2 (x^2 + 12x + (12/2)^2 - (12/2)^2) - 70
f (x) = -2 (x^2 + 12x + 36 - 36) - 70 <--- distribute the -2 onto -36 to get it out of the brackets..
f (x) = -2 (x^2 + 12x + 36) + 72 - 70 <-- combine constants and factor perfect square trinomial...
f (x) = -2 (x + 6)^2 + 2 <-- standard form...
Answer:
25
Step-by-step explanation:
Using 3.14 for PI.
The radius of a ball and the can is half the diameter = 1.25
The height of the can is the height of 3 diameters = 7.5
Volume of one tennis ball:
4/3 x PI x 1.25^3 = 8.18 cubic inches.
Volume of 3 tennis balls: 3 x 8.18 = 24.54 cubic inches.
Volume of can:
PI x 1.25^2 x 7.5 = 36.80 cubic inches.
Space = 36.80 - 24.54 = 12.26 cubic inches.
Answer:
1.B 2.D 3.C 4.A
Step-by-step explanation: